Anorexia nervosa: un estudio de casos - Zusman, Lillyana (1990)
Anorexia Nervosa is an Eating Disorder defined (etimoligacally) as a "nervouse loss of apetite". It is characterized by a conscious, voluntary and categoric attitude of the sick patient to refrain from eating. He/she has a firm conviction of having excess weight which they try to modify by starvation.Through a case study, a distinction between two types of Anorexia Nervosa is proposed: a Structural Anorexia Nervosa -in which an intrapsyhic, primary, arcaic conflic prevails, leading to an isolated, withdrawal conduct- and a Reactive Anorexia Nervosa, in which a later intrafamilial conflict prevails leading, therefore, to a more open personality, compatible with the enviroment.